PENYELESAIAN SENGKETA PENUNDAAN PEMBAYARAN UTANG DENGAN ALASAN PANDEMI COVID-19 MELALUI PUTUSAN PERDAMAIAN PKPU(Studi Kasus Putusan PKPU Nomor: 46/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst ) - Nandien Dwiputri (2023)
The Covid-19 pandemic has caused losses in various fields, especially the economy. The impact of the Covid-19 pandemic resulted in only 58.95% of companies being able to operate normally, in fact as many as 82.45% of companies experienced a decrease in revenue. Based on Presidential Decree Number 12 of 2020 concerning Stipulation of Non-Natural Disasters from the Spread of Corona Virus Disease 2019 (Covid-19) as National Disasters as a legal basis for force majeure. With so many companies having an impact, an increase in bankruptcy and PKPU cases has occurred due to defaults committed by debtors due to Covid-19. For example, not carrying out obligations, such as paying debts due to a declining company's financial situation. As in the case of the PKPU Peace Decision Number: 46/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst. Where based on the case it is known that the Debtor cannot fulfill his performance obligations because one of the reasons is being affected by Covid-19. So based on these problems the author obtains the formulation of the problem, namely: Can the condition of the Covid-19 pandemic be a reason for delaying debt payments by debtors and how is the implementation of the PKPU conciliation decision Number 46/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst in the case of a request for postponement of debt payments. The research method used by the author in this study is normative juridical by adhering to theories and laws and regulations. As well as using a statutory problem approach and cases based on primary and secondary legal data sources. Equipped with qualitative analysis techniques. The results of the study show that the Covid-19 pandemic does not automatically eliminate debtors' obligations to fulfill their achievements when the Covid-19 pandemic is declared by the government to have ended. And in the PKPU decision, the fourth condition was not met because both debtors and creditors both suffered losses due to the Covid-19 pandemic.